RCCD1 depletion attenuates TGF-β-induced EMT and cell migration by stabilizing cytoskeletal microtubules in NSCLC cells. (1st August 2017) - Wu, Junyu; He, Zhimin; Yang, Xiao-Mei; Li, Kai-Le; Wang, Da-Liang; Sun, Fang-Lin
Abstract: Lung cancer is one of the most lethal cancers due to its highly metastatic spreading. The motility of lung cancer cells is regulated by paracrine factors, such as TGF-β, in the tumor microenvironment through the induction of epithelial-to-mesenchymal transition (EMT). The stability of microtubules is reported to be associated with the EMT process and the migration of cancer cells. Here, we observed that RCC1 domain-containing protein 1 ( RCCD1 ) is highly expressed in non-small cell lung cancer (NSCLC) patients with poor prognosis, and RCCD1 is much higher expressed in tumor tissues compared with adjacent normal tissues. Depletion of RCCD1 using siRNAs significantly inhibits the migration of lung cancer cells. Subsequent studies reveal that the loss of RCCD1 results in upregulation of acetylated α-tubulin levels and stabilizes cytoskeletal microtubules. Mechanistically, we observed that RCCD1 modulates the stability of microtubules through interacting with JMJD5. Furthermore, RCCD1 depletion significantly attenuates the TGF-β-induced EMT process, as assessed by altered expression of epithelial and mesenchymal markers ( Occludin, Vimentin and Snail ), and inhibits TGF-β-induced cell migration. Collectively, these findings support RCCD1 as a novel regulator of TGF-β-induced EMT in NSCLC. Highlights: RCCD1 is highly expressed in NSCLC patients with poor prognosis. Depletion of RCCD1 inhibits the migration of NSCLC cells. RCCD1 depletion increases the stability of cytoskeletal microtubules. RCCD1 modulates microtubule stability through interacting with JMJD5. RCCD1 depletion attenuates TGF-β-induced EMT progression.